Managing, Marketing, and Maintaining Maritime and Coastal Tourism - Brito, Mónica (2021)
Managing, Marketing, and Maintaining Maritime and Coastal Tourism is a pivotal reference source that provides vital material on the application of multidisciplinary and interdisciplinarity logic surrounding sea tourism. While highlighting topics such as destination marketing, event management, and global business, this publication explores the dynamic capabilities and the methods of overall management of hospitality by the sea. This book is ideally designed for marketers, advertisers, tour directors, cruise directors, travel agents, port managers, coastal cities managers, event coordinators, academics, students, researchers, policymakers, public managers, and tourism entrepreneurs.